Social, Economic, and Environmental Impacts of Sentul Rain Forest Tourism Development - Khairunnisa Luthfiyah; Bramasto Nugroho (Institut Pertanian Bogor, 2025)
Sentul Rain Forest Tourism (SRFT) is one of the ecotourism objects developed in a forest area managed by Perhutani Public Company in collaboration with a private company. This study examined the social, economic, and environmental impacts of SRFT on the surrounding community before and after SRFT development. The study used quantitative descriptive analysis methods, with interviews and questionnaires. Respondents were divided into two groups: community groups receiving direct and indirect impacts. The results showed that SRFT had a positive social impact, namely increasing social accessibility, which can increase people's mobility. Economically, SRFT created jobs and increased people's income in community groups with direct and indirect impacts. Environmentally, it increased the tree covering and positively changed people's attitudes towards forest management. However, the development of SRFT also has a negative impact. Socially, increasing conflict between tourists and the community, both in the community groups receiving direct and indirect impacts. Economically, it increased the externality costs to community groups that receive direct impacts. Keywords: economy impact, ecotourism, environmental impact, rain forest, social impact